Framing Climate Crisis: A Critical Discourse Analysis of Climate Change Narratives in Pakistani English Newspapers - Muhamad Saad Jan; Awais Bin Wasi; Suliman Ali (ASIAN Journal of International Peace & Security (AJIPS), 2025)
Climate change represents a serious and growing threat to developing nations, especially Pakistan, where extreme weather events have become very frequent and disruptive. This paper examines the ways in which the editorials of the Pakistani English-language newspapers framed recent climate-related incidents in May 2025, when the country experienced a series of severe hailstorms and unusual weather patterns in major cities. The study employs a qualitative analysis of four editorials published in Dawn, The Nation, Islamabad Post, and Pakistan Today, informed by framing theory and guided by Fairclough’s three dimensional model of Critical Discourse Analysis (CDA). The discussion of how responsibility and causality are presented is based on the analysis of lexical choices, metaphorical constructions, agency assignment and discursive silences. The findings show that the selection of framing is very diverse and that in general, it leans towards framing vague or passive constructions that blur institutional accountability. Moreover, the issue of climate justice and social inequity remains minor, and vulnerable groups and structural conditions are not considered seriously. The analysis shows that editorials serve as powerful ideological sources that influence the public perception of climate crises. It emphasizes the necessity of having more responsible and justice-oriented editorial discourse in the Pakistani media.